Side-to-side caval anastomosis in a patient receiving a liver graft from a marginal donor with situs inversus totalis. (2015) - Manzia, Tommaso Maria; Tariciotti, Laura; Angelico, Roberta; Toti, Luca; Anselmo, Alessandro; Tisone, Giuseppe
Highlights: Liver transplantation using a donor with situs inversus totalis is feasible and safe. The anatomical anomalies in the donor with situs inversus totalis should not be considered a controindication to liver transplantation. The 1992-Belghiti piggyback technique represents an excellent surgery option for liver transplantation. Abstract: Introduction: The donor situs inversus totalis status was considered an absolute contraindication to liver transplantation due to the technical difficulties involved. Only in recent years has a very young deceased donor with situs inversus totalis been considered as a potential donor. Presentation of case: We herein report a single case of 57-year-old male patient with hepatocellular carcinoma who received a liver transplantation from a 73-year-old woman with situs inversus totalis. Liver was implanted using a 1992-Belghiti piggyback technique positioning the larger hemiliver in the left upper quadrant and the left in the liver fossa. We assisted a good graft reperfusion without surgical or anesthetic problems. His hospital stay was relatively uneventful and he was discharged from hospital on postoperative day 7. At 8 months of follow-up the patient is alive and in good clinical condition. Discussion: The donor situs inversus totalis does not require any modification of transplant procedure if the donor–recipient size match permits a comfortable placement of the graft in a standard anatomical position. To the best of our knowledge, this is the first case of liver transplantation with a graft from a "marginal" donor with situs inversus totalis using a 1992-Belghiti piggyback technique. Conclusion: The donor situs inversus totalis status should not be considered a contraindication for LT and the piggyback technique should be considered the surgery of choice.